Optimization of HIFU monotherapy for prostate cancer - K. V. Pozdnyakov; V. V. Bazaev; V. V. Dutov (Вестник урологии, 2022)
Introduction. One of the most researched alternative treatments for localized prostate cancer (PCa) is ultrasound ablation (HIFU ¾ High-intensity Focused Ultrasound). Although the world history of the application of this method of PCa treatment is more than 15 years old, the scope of the application of the method has not finally been determined.Purpose of the study. To study the results of the application of ultrasound ablation in the treatment of patients with localized and locally advanced PCa.Materials and methods. The study included 147 patients with PCa who underwent HIFU treatment using the AblathermÒ device («EDAP TMS», Vaulx-en-Velin, Lyon, France). Group 1 included patients with localized and locally advanced PCa treated at the stage of gaining experience and evaluating the results of treatment (n = 82). Group 2 consisted of patients with localized PCa of low and moderate oncological risk (n = 65). The number of sessions in group 1 varied from 1 (65) to 2 (17). The need to perform a second session was associated with the ineffectiveness of the first. HIFU was also performed after the failure of external beam radiation (2), and photodynamic (1) therapy. In group 2, 61 patients received one treatment session, 4 patients received 2 sessions each. The mean follow-up time for the patients in group 1 was 17.4 ± 5.2 (3 – 29) months, for group 2 was 18.2 ± 7.3 (3 – 29) months.Results. In group 1 of patients with a low degree of oncological risk, a decrease in blood prostate-specific antigen (PSA) below the threshold value and the absence of its significant increase during the observation period was noted in 87.5% of cases (28 patients), with an average degree of oncological risk in 65.6% of cases (21 patients), with a high degree in 27.7% of cases (5 patients). In 34.1% (28 patients), the treatment was ineffective, 21 of them underwent repeated ultrasound ablation of the prostate, and 7 patients received subsequent external beam radiation therapy. These results led us to abandon the use of HIFU in patients with baseline blood PSA levels greater than 20 ng/ml and locally advanced disease. In group 2, biochemical recurrence was noted in 9 patients. A control biopsy in 6 patients confirmed local recurrence, which became the basis for a second HIFU session (4). Five patients received adjuvant hormonal therapy. The total effectiveness of the treatment in group 2 was 86.2%.Conclusion. The results support the notion that HIFU is a treatment option for localized PCa only. The evaluation of the initial results led us to abandon treatment with this method in patients with locally advanced and high-risk localized PCa.